Implementation of Learning Services in an Effort to Understanding Students' Learning Styles - Chairuni, Alfi; Jamaaluka Surea, Alam; Syahfanny, Dewi; Lesmana, Gusman (Berpusi Publishing, 2023)
Student learning style is a way that becomes individual characteristics in processing information and understanding learning material. Learning styles are influenced by natural factors and environmental factors. Therefore, it is important for educators to know the learning styles of their students so that they can provide learning that suits the needs and characteristics of students. The learning styles most used by outstanding students are intuitive and sensory learning styles. Tutoring services can be an effort to understand students' learning styles. Tutoring services can assist students in optimizing development and overcoming problems in the process of learning with teachers and independent learning both at home and at school. However, the implementation of tutoring services is still experiencing problems, such as limited understanding, time, and teacher skills. In order to improve student learning outcomes, educators need to pay attention to the diversity of student learning styles and accommodate them with appropriate methods and strategies. Tutoring services can be an alternative in understanding students' learning styles and assisting students in optimizing development and overcoming problems in the learning process.